Citrus mites in Italy I. Species collected and key of orders, suborders and families (Bollettino di zoologia agraria e bachicoltura, 2024)
The results of a research on mites of Citrus in Italy are presented. The research has been carried out on various species of Citrus in main agricultural areas of Italy, and the collection of 64 species belonging to 17 different families has been possible.The initial contribution gives the key to the identification of orders, suborders and families.